Into the furniture woods: Analytical hierarchy process method - Kumar R.; Ayshwarya B.; Muslihudin M.; Nguyen P.T.; Alfian F.Y.; Hashim W.; Shankar K.; Hafizah S.; Mukodimah S.; Odarich I.N.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Sidojaya Furniture is one of the Small and Medium Enterprises that is still developing in improving its business. Related with the lack of information obtained by furniture craftsmen in determining qualified wood, Sidojaya Furniture has problems in determining qualified wood that matches with specified criteria for making furniture quickly and accurately. The objective to be achieved from this study was to create Decision Support System for selecting qualified wood in Sidojaya Furniture using AHP (Analytical Hierarchy Process) Method and using Microsoft Visual Basic programming language that can help provide information about qualified wood for furniture production, so that craftsmen can make decisions quickly to make choice. AHP method is a method of breaking complex/ complicated problem in unstructured situation into component parts. Decision support system for the selection of qualified wood can make it easier for craftsmen to decide on the type and nature of qualified wood and obtain information about the texture, color, direction of fiber, age, durability and growing place of wood to be used. From three alternatives tested, it can be obtained, the decision of qualified wood can be used to make furniture was teak wood with a weight score of 1.389. BEIESP.